Effect of tool rotational speed on force generation, microstructure and mechanical properties of friction stir welded Al-Mg-Cr-Mn (AA 5052-O) alloy - Moshwan, Raza; Yusof, Farazila; Hassan, Mohamed Mohsen Abdel-Naeim; Rahmat, Sahifulddin M. (Elsevier, 2015)
Friction stir welding (FSW) between 3 mm thick AA 5052-O aluminum alloy plates was investigated in the present study. Different welded specimens were produced by employing a constant tool traverse speed of 120 mm/min and by varying rotating speeds from 800 to 3000 rpm. The welded joints were characterized by its appearances, microstructural and mechanical properties at room temperature. The measurement of different forces acted on the tool during the FSW of AA 5052-O plates provided a significant insight to determine the quality of the welded joints. From the appearances of the welded joints it was evident that, except the tool rotational speed of 3000 rpm all other rotational speeds produced sound welded joints with smooth surface. The joint produced at 1000 rpm yielded a maximum tensile strength of 132 MPa which was 74 of the base material strength. Field emission scanning electron microscopy (FESEM) and energy dispersive spectroscopy (EDS) analyses on the stir zone suggested that, beta-Mg2Al3 intermetallic phases of the base material were mechanically fractured, smeared and mixed to different geometries due to tool stirring. The dissolution and redistribution of beta-Mg2Al3 second phase particles in the stir zone had a considerable effect on the reduction of the tensile strength of the welded joints. The reduction in hardness at the nugget zone (NZ) of the welded joints under different tool rotational speeds could be attributed to the dislocation of Mg-rich phases and segregation of Mg solute atoms at grain boundaries, which drew solute Mg atoms away from the alpha-aluminum matrix. (C) 2014 Elsevier Ltd. All rights reserved.